2017
DOI: 10.1002/ptr.5964
|View full text |Cite
|
Sign up to set email alerts
|

Citrus essential oils inhalation by mice: Behavioral testing, GCMS plasma analysis, corticosterone, and melatonin levels evaluation

Abstract: The use of orange essential oils (EOs) as a complementary treatment is very common in Brazilian popular culture. The levels of melatonin (MEL) and corticosterone (CORT) hormones were investigated simultaneously, by the Luminex™ immunoassay system in mice plasma, after Citrus aurantium and Citrus sinensis EOs inhalation for 30 min. The plasma was analyzed by headspace through gas chromatography coupled to mass spectrometry for investigation of the EO components. Mice were submitted to behavioral testing to rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 29 publications
1
20
0
2
Order By: Relevance
“…In this line, the present results suggested that NO inhibition plays an important role in this effect. Furthermore, the present results corroborated (and extended to other models) previous study indicating an anxiolytic‐like effect of C. sinensis in animal models of anxiety (Faturi et al, ; Wolffenbüttel et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this line, the present results suggested that NO inhibition plays an important role in this effect. Furthermore, the present results corroborated (and extended to other models) previous study indicating an anxiolytic‐like effect of C. sinensis in animal models of anxiety (Faturi et al, ; Wolffenbüttel et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…This anxiolytic‐like effect of C. sinensis essential oil was already observed in the elevated plus‐maze and light/dark test (Faturi et al, ; Wolffenbüttel et al, ). In rats, C. sinensis essential oil increased the open arms exploration in the elevated plus maze and spent more time in the lit side of light/dark apparatus.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations